Pengaruh Brand Image, Kualitas Produk, Harga dan Diskon Terhadap Keputusan Pembelian Sepatu Merek Fladeo (Studi pada Mahasiswa Universitas Kanjuruhan Malang) - Uwis Ayu Wandary; Rusno Rusno; Candra Wahyu Hidayat (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2018)
The study aims to determine the effect of brand image, product quality, price, and discount on purchasing decisions fladeo brand shoes. This research was conducted in university kanjuruhan malang, the population in this study were students who had bought or used fladeo brand shoes and a sample of 114 students. Sampling technique in this study using accidental sampling method and data obtained from questionnaires distributed to respondents. The research instrument test was tested for validity and reliability. The data analysis technique used is multiple linear regression with SPSS. The results of the study show that simultaneously the brand image, product quality, price, and discount have a significant effect on purchasing decisions, partially brand image has a significant effect on purchasing decisions, product quality has a significant effect on purchasing decisions, price has a significant effect on purchasing decisions, discount have no significant effect on purchasing decisions.